Zmiana zakresu zakazu prowadzenia pojazdów mechanicznych w postępowaniu wykonawczym - Łucarz, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The presented study treats about the possibility of changing the scope of ban at the executory proceedings stage, introduced by the Act of 20 March 2015, of amending the Penal Code and some other acts. The authoress introduces details of this regulation, pointing out certain inaccuracies which are featured by her.
Keywords: polskie prawo karne; postępowanie egzekucyjne; zakaz prowadzenia pojazdów